Predictors of Loss to Follow-up in Hip Fracture Trials: A Secondary Analysis of the FAITH and HEALTH Trials. (November 2020) - Sivaratnam, Surabhi; Comeau-Gauthier, Marianne; Sprague, Sheila; Schemitsch, Emil H.; Poolman, Rudolf W.; Frihagen, Frede; Bhandari, Mohit; Swiontkowski, Marc; Bzovsky, Sofia
Abstract : Background: Hip fracture trials often suffer substantial loss to follow-up due to difficulties locating and communicating with participants or when participants, or their family members, withdraw their consent. We aimed to determine which factors were associated with being unable to contact FAITH and HEALTH participants for their 24-month follow-up and to also determine which factors were associated with their withdrawal of consent. Methods: We conducted 2 multivariable logistic regression analyses to determine which factors were predictive of being unable to contact participants at 24 months postfracture and withdrawal of consent within 24 months of their fracture. Results were reported as odds ratios, 95% confidence intervals, and associated P -values. All tests were 2-tailed with alpha = 0.05. Results: We were unable to contact 123 of 2520 participants (4.9%) for their 24-month follow-up visits and 124 (4.9%) withdrew their consent from the trial. Being non-White ( P = 0.003), enrolled from a non-European hospital ( P < 0.001), and treated with arthroplasty ( P < 0.001) were associated with an increased odds of not completing the 24-month follow-up visit. Being enrolled from a hospital in the United States ( P = 0.02), from a hospital in Oceania, India, or South Africa ( P < 0.001) as compared to a European hospital, and treated with arthroplasty ( P < 0.001) were associated with an increased odds of consent withdrawal. Discussion: Certain factors may be predictive of loss to follow-up in hip fracture trials. We suggest that the identification of such factors may be used to inform and improve retention strategies in future orthopaedic hip fracture trials. Level of Evidence: Prognostic Level II. See Instructions for Authors for a complete description of levels of evidence.